2019
DOI: 10.1002/bit.26962
|View full text |Cite
|
Sign up to set email alerts
|

Impact of protein blocking on enzymatic saccharification of bagasse from sugarcane clones

Abstract: Lignin plays an important functional and structural role in plants, but also contributes to the recalcitrance of lignocellulosic biomass to hydrolysis. This study addresses the influence of lignin in hydrolysis of sugarcane bagasse from conventional bred lines (UFV260 and UFV204) that were selected from 432 field-grown clones. In addition to higher sugar production, bagasse clone UFV204 had a small, but statistically significant, lower insoluble lignin content compared with clone UFV260 (15.5% vs, 16.6%) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
1
13
1
Order By: Relevance
“…The soluble phenolic compounds derived from the higher severity pretreatment decreased cellulolytic activity to a significantly greater degree than the inhibition resulting from pretreatment with a severity factor of 3.83 [28]. The chemical composition data of SCB here differs from our previous work, where it had higher cellulose (49%-51%), hemicellulose (24%-25%), and lower lignin (23%-25%) components in the initial SCB [8]. This likely reflects the normal variation that will occur under differing growth conditions year to year and field to field.…”
Section: Chemical Composition Of Liquid Hot Water Pretreated Sugarcancontrasting
confidence: 84%
See 4 more Smart Citations
“…The soluble phenolic compounds derived from the higher severity pretreatment decreased cellulolytic activity to a significantly greater degree than the inhibition resulting from pretreatment with a severity factor of 3.83 [28]. The chemical composition data of SCB here differs from our previous work, where it had higher cellulose (49%-51%), hemicellulose (24%-25%), and lower lignin (23%-25%) components in the initial SCB [8]. This likely reflects the normal variation that will occur under differing growth conditions year to year and field to field.…”
Section: Chemical Composition Of Liquid Hot Water Pretreated Sugarcancontrasting
confidence: 84%
“…In this work, we have demonstrated that even relatively small differences in lignin content can result in considerably increased sugar production, which supports the dissimilarity of bagasse lignin content and its effects on cellulose digestibility. The increased glucose yields with the addition of BSA helped to decrease the inhibition of non-productive absorption of cellulose enzymes onto lignin and solid residual lignin fractions.Molecules 2020, 25, 623 2 of 12 biofuel production [4,[6][7][8][9][10]. In particular, the physical barrier of lignin prevents enzyme access to cellulose and hemicellulose.…”
mentioning
confidence: 99%
See 3 more Smart Citations